Effective pulmonary blood flow in normal children at rest. Issue 12 (December 1988) - Bowyer, J J; Warner, J O; Denison, D M
Abstract : Effective pulmonary blood flow was measured with a soluble inert gas uptake method (10% argon, 3.5% freon-22, 35% oxygen, balance nitrogen) in 98 apparently healthy children aged 5-14 years. None had any evidence of cardiorespiratory disease and all had normal values for absolute and dynamic lung volumes and transfer factor for carbon monoxide. Values of blood flow measured by a rebreathing method correlated reasonably closely with height, weight, body surface area, and lung volumes, and to a lesser extent with hand and foot size. The mean (SD) effective pulmonary blood flow index was 2.7 (0.31) 1 min-1 m-2. Small children found a single breath method of measuring flow more difficult to perform and the results were more variable.